PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE ( TTW ) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI SMA NEGERI 1 PAINAN TAHUN PELAJARAN 2013/2014 - Rosa, Dgas Dapeta Lana (STKIP PGRI Sumbar, 2014)
The learning of biology in SMAN 1 tends to be monotonous. This matter causes the lower result oflearning biology for students. One of its causes is that the teachers there do not use a model of learning which isvaried, so the students get the lack of interest and motivation to learn. To overcome the matter, it is necessary toapply one way to make the students there active and motivated in learning, which by implementing cooperativelearning model of Thing Talk Write toward the result of XI grade students in studying biology in SMAN 1Painan. This research is an experiment research by using a design of Randomized Control Group Posttest OnlyDesign research. The population of this research is all XI grade students of SMAN 1 Painan Academic Year2013/2014. The taken sample is done with Purpose Sampling, so it is chosen for XI1 grade (experiment class)and XI2 (controlled class). The data of this research is the result of students learning which overwhelmscognitive competence only. Based on last test, it can be concluded that cooperative learning model of Thing TalkWrite can improve the learning result of biology toward XI grade students in SMAN 1 Painan.